Making the world a better place with fintech research. (15th March 2021) - Lagna, Andrea; Ravishankar, M. N.
Abstract: Financial technology (fintech) is seen as possessing significant potential to provide the poor access to financial services and help them escape the clutches of poverty. Surprisingly, Information Systems (IS) research has engaged little with fintech's promise of fostering financial inclusion for the poor. In the spirit of 'making a better world with ICTs', conducting 'responsible IS research for a better world' and 'understanding and tackling societal grand challenges through management research', we advance a framework for guiding IS research on fintech‐led financial inclusion. Drawing on the IS literature and Information and Communication Technologies for Development (ICT4D) scholarship, we extrapolate five areas of research that can better illuminate fintech's contributions to financial inclusion: (a) business strategies for fintech‐led financial inclusion; (b) digital artifacts of fintech‐led financial inclusion; (c) business environment of fintech‐led financial inclusion; (d) microfoundations of fintech for financial inclusion; (e) developmental impacts of fintech. We conclude with a discussion of how the five areas offer opportunities for impactful research on fintech and the promise of building a financially inclusive society.